Pelatihan Menjadi Guru Reflektif yang Inovatif Melalui “Deep Learning” - Irawan, Ferry; Hanip, Rival (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Reflection activities are very important activities to be carried out because they will control the teacher's actions, the teacher can see what still needs to be fixed, improved or maintained. It is an activity that needs to be done when the teacher as a field practitioner has finished taking action, this is a form of self-evaluation. The teacher conveys all activities or experiences that have been carried out to be discussed with the researcher, the teacher conveys everything that has been felt and conveys the extent of the progress or progress of the actions taken. In carrying out reflection activities, teachers, in addition to acting as researchers themselves, must also collaborate with teachers of the same subject but different classes or researchers from universities so that reflection can be carried out to the stage of interpreting actions and situations in existing learning so that it can provide a basis for improving the action plan that will be carried out next. Being a reflective teacher means continuing to reflect on what has been done. The same thing is that the method or approach taken by the teacher where he explores what is done and why he does it is part of the reflective approach in teaching. Meanwhile, the reflective process is "a continuous process in reflecting on "received knowledge" and "experiential knowledge" in the context of professional action (practice)".